Stomal stenosis during gradual closure of a traumatic abdominal wall hernia. (2019) - Suzuki, Mitsuhiro; Matsushima, Hisao; Uehara, Katsuki; Saiki, Tatsuhiko; Hayamizu, Atsuki; Kamisasanuki, Toshirou; Sugiki, Daisuke
Highlights: Stomal stenosis can develop after repair of a traumatic abdominal wall hernia. Abdominal wall repair with negative-pressure wound therapy may be effective. Stomal patency must be evaluated during the abdominal wall hernia repair. Abstract: Introduction: Traumatic abdominal wall hernias are often accompanied by intra-abdominal injuries, and a stoma may be required. Although rare, stomal stenosis can develop after the repair of a traumatic abdominal wall hernia. Presentation of case: A 65-year-old woman was in a head-on collision with a truck and was brought by ambulance to our facility. The findings of a physical examination and computed tomography scan suggested bowel perforation for which exploratory surgery was performed. The lacerated small bowel and sigmoid colon were resected and an ileostomy and colostomy were created. Abdominal wall reconstruction was impossible because of the large defect size. Repair of the abdominal wall was achieved by gradual closure of the fascia after surgery in combination with negative pressure wound therapy. Stenosis of the ileostomy occurred during this process and was surgically repaired. Discussion: We reconstructed the abdominal wall using negative pressure wound therapy in combination with sutures while minimizing the risk of abdominal compartment syndrome. This approach did not increase the intra-abdominal pressure, but it deformed the abdominal wall, resulting in unexpected stenosis of the ostomy. Conclusion: Gradual postoperative closure of a traumatic abdominal wall hernia with an ostomy in place may result in stomal stenosis. Stomal patency must be carefully evaluated during this process.